PRACTICAL BENEFITS OF INFORMATION MODELING OF BUILDINGS - Ikramov Shovkat Rustamovich; Safiyev Timur Shamilevich (Galaxy International Interdisciplinary Research Journal, 2022)
BIM building data modeling is actively used by many construction companies as an effective tool for coordination, visualization, communication, site management, collection and marketing. Using BIM construction information modeling technology, it is possible to create a virtual model of the building and track all the processes related to construction. Team members, planning engineers, architects, project coordinators, project managers and stakeholders can easily understand the project being built. In this article, we review the advantages of bim construction data modeling in the construction industry for owners and contractors.